Climate, peace and security: Kenya - Pacillo, Grazia; Läderach, Peter; Takaindisa, Joyce (2024)
Climate security explores whether climate change increases the risk of armed conflict and, if so, under which circumstances this relationship occurs. People in fragile and conflict-affected areas are also among the most vulnerable to climate change, making it vital to understand the climate-conflict interplay for resilience and peacebuilding. A major challenge for governments in vulnerable, fragile, and conflict-affected regions is managing these complex interactions. Currently, they lack effective tools to implement climate strategies that address social grievances driving conflict and adapt to changing dynamics. In response, conflict-sensitive approaches to climate action are gaining support as mechanisms to ensure transitions to carbon-neutral economies and climate-resilient societies are equitable and aligned with peacebuilding goals. This report summarizes five intersection pathways between climate, peace and security in Kenya, which were developed through a multiple methods approach. It also puts forward a set of policy and porgramming recommendations towards climate action the mitigates underlying drivers of conflict and contributes to a suatianable peace.